DC‐contact radio‐frequency microelectromechanical system symmetric toggle switch on a borofloat substrate. (1st May 2013) - Li, Ling; Hou, Zhihao; Zhao, Chenxu; Liu, Zewen
Abstract : Presented is a DC‐contact radio‐frequency (RF) microelectromechanical system symmetric toggle switch for broadband power applications. Based on the lever principle, the proposed switching structure can be toggled upwards with extra restoring force using push electrodes. This push mechanism greatly improves the isolation and efficiently avoids the down‐state stiction of the contacts which leads to enhancement of the power‐handling capability. The measured actuated voltage is 33.4 V and the contact resistance of the switch can be further decreased to 0.18 Ω under a pull in voltage of 60 V, which results in the improvement of insertion loss. The switch can be properly restored with a voltage of 30 V applied to the push electrode. In addition, the substrate loss is reduced by using a Boroloat™ glass substrate. The RF measurement results show that the switch can handle a minimum 1 W incident RF signal power with isolation and an insertion loss of better than −30 and −0.24 dB from DC to the X‐band.